Biogenic synthesis of zinc oxide nanoparticles using NARC G1 garlic (Allium sativum) extract, their photocatalytic activity for dye degradation and antioxidant activity of the extract - Muhammad Usama Younas; Munawar Iqbal; Naveed Ahmad; Shahid Iqbal; Abida Kausar; Arif Nazir; Osama A. Mohammed; Fozia Anjum (Results in Chemistry)
Nanotechnology offers innovative solutions to challenges across various fields, including medicine, catalysis and environmental remediation. Zinc oxide nanoparticles (ZnO-NPs) have attracted considerable interest in biomedical and photocatalytic applications. In this study, ZnO-NPs were fabricated using a green method with NARC G1 garlic (Allium sativum) plant extract. These nanoparticles (NPs) were appraised for their valuable characteristics employing UV–visible spectroscopy, Fourier-Transform infrared spectroscopy (FTIR), particle size analyzer (PSA), scanning electron microscopy (SEM) and X-ray diffraction (XRD) and. UV–Vis spectra demonstrated an absorption peak at 370 nm. In comparison, PSA revealed an average particle size of approximately 20.0 nm. SEM analysis confirmed irregular morphology and XRD identified the hexagonal crystalline structure of NPs. The FTIR analysis showed a peak at 570 cm−1 indicating the presence of the zinc oxide (ZnO) functional group. The photocatalytic activity of RB-5 dye was observed under sunlight. The extract yield recovered from different solvents ranged between 4.52 and 6.74 g/100 g. The total phenolic content (TPC) and total flavonoid content (TFC) in the NARC G1 garlic extract were quantified, ranging from 266–379 mg GAE/100 g and 152–242 mg CE/100 g, respectively. Among the tested solvents, aqueous ethanol showed the maximum extraction efficacy for inhibiting linoleic acid oxidation. This study highlights the significant bioactive potential of NARC G1 garlic, which can be used in the nutraceutical industry. Moreover, this research supports the use of NARC G1 garlic as a green-reducing agent for the synthesis of ZnO-NPs. The promising photocatalytic activity of these NPs demonstrates their capacity for technologies used in environmental remediation.